Eastern Polissian Patois in the Novel «Leaves of the Earth» by Volodymyr Drozd: Phonetic Aspect (Linguostylistic Studies, 2017)
The article deals with the analysis of the individual author’s specificity of the usage of the Eastern Polissian patois in the novel «Leaves of the Earth» by Volodymyr Drozd. The author lays emphasis on the dialect units of  the phonetic level and comments them in terms of origin. The author highlights functional efficiency of the dialectal elements in the literary language and the degree the literary work is saturated with them. The dialect units are analyzed regarding their correlation with a specific type of the literary work language - the language of characters or the author’s language.  It was found out that Volodymyr Drozd uses dialect units of different levels in lengthy narratives and characters’ memoirs. The author’s language mostly corresponds to the Ukrainian language literary standard. The Polissian dialect elements in the text of the novel contribute to the linguistic expressiveness, persuasiveness and accuracy of conveying the local language coloring, as well as ethnographic and linguistic identity of the characters.
Keywords: literary language; literary text; Volodymyr Drozd; dialect; northern dialect; Eastern Polissya patois